"It was my own decision": the transformational shift that influences a woman's decision to use contraceptives covertly - Jenna Hoyt; Jessie K. Hamon; Shari Krishnaratne; Emmanuel Houndekon; Dora Curry; Miriam Mbembe; Seth Marcus; Misozi Kambanje; Shannon Pryor; Ariko Angela Barbra; Herbert Muhumuza; Nathaly Spilotros; et al. (BMC, 2022)
Abstract Background Family planning (FP) is an important element of sexual and reproductive health and rights, but socio-cultural barriers and unbalanced gender relations often limit women's decision-making about contraceptive use. Covert contraceptive use (CCU) exemplifies the limits on women's decision-making and represents a way in which some women overcome constraints to achieve their reproductive goals. This study explores the decision-making process through which women choose to use contraceptives covertly. Methods A qualitative synthesis was conducted using data from women, health providers, community members, health administrators, and intervention implementers (n = 400) to explore the decision-making process through which women choose to use contraceptives covertly. Interviews and focus group discussions were conducted at two time points as part of an evaluation of interventions integrating FP and childhood immunisation services at sites in Benin, Kenya, Malawi and Uganda. The sexual and reproductive health empowerment framework by Karp et al. (2020) was adapted and used to guide the analysis. Results Women recognised that although they suffered the negative consequences of frequent pregnancies and of raising large families, they lacked overt decision-making power over their fertility. Women were confident to engage in CCU because they believed their husbands did not understand these consequences nor acknowledged their suffering, which justified not informing them. CCU was a difficult choice however, women felt comfortable voicing their reproductive preferences in settings where health providers were supportive. Conclusions Women chose to use contraceptives covertly when they questioned the unfairness of their situation and recognised their own power to act in accordance with their reproductive preferences. This represented an important shift in a woman's perception of who is entitled to make decisions about contraceptive use. Importantly, health providers can play a key role in supporting women's autonomous decision making about contraceptive use and should be careful not to undermine women's confidence.